Implementasi Pendidikan Karakter Beriman Bertakwa Kepada Tuhan YME Melalui Pembiasaan SD Islam Al Madina - Khoirotun Nashihah; Duwi Nuvitalia; Arfilia Wijayanti; Azri Setyo Rini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the implementation of character education of faith and piety to God Almighty through Islamic boarding school-based habituation at Al Madina Islamic Elementary School. The approach used is qualitative. Data collection techniques using observation, interviews, questionnaire, and documentation. Data analysis technique uses Miles and Huberman analysis. Test the validity of the data by triangulation and adequacy of references. The formation of the character of faith and piety to God Almighty is important and fundamental as an effort to avoid the moral crisis of students as the next generation of the nation as a result of the times. The results of the study show that the implementation of the character education of faith and piety to God Almighty through Islamic boarding school-based habituation at Al Madina Islamic Elementary School through morning call activities and group prayers, memorizing letters and hadiths, dhuha prayers, midday prayers in congregation, and mujahadah activities.